2019
DOI: 10.11604/pamj.2019.33.284.18338
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus genotypes in cervical cancer in Maiduguri, Nigeria

Abstract: IntroductionCervical cancer is the commonest gynaecological malignancy and the second most common cancer among women worldwide. Several epidemiological, clinical and molecular studies have strongly implicated oncogenic high-risk human papillomavirus infection in the aetiopathogenesis of cervical cancer. The objectives of this study were to determine the cervical HPV prevalence and genotype distribution in cervical cancer in Maiduguri, Nigeria.MethodsThis was a descriptive and retrospective study. Sixty-three a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 44 publications
1
19
2
Order By: Relevance
“…All the same, the most predominant HPV genotype in the present study, HPV31, is in concordance with the outcome of Neto et al [35]. Again, in Maiduguri, a Muslim dominated city in northern Nigeria, Kabir et al [36] reported 69.8% prevalence rate of HPV using DNA detection method. Also, a robust review study of several low-resource countries by Nweke et al [37] shows that sub-Saharan African has high prevalence rates of HPV infection predominated with three high-risk genotypes, HPV-16, 18, and 45, two of which were also detected in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…All the same, the most predominant HPV genotype in the present study, HPV31, is in concordance with the outcome of Neto et al [35]. Again, in Maiduguri, a Muslim dominated city in northern Nigeria, Kabir et al [36] reported 69.8% prevalence rate of HPV using DNA detection method. Also, a robust review study of several low-resource countries by Nweke et al [37] shows that sub-Saharan African has high prevalence rates of HPV infection predominated with three high-risk genotypes, HPV-16, 18, and 45, two of which were also detected in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…carcinoma of the cervix uteri is among the most preventable malignancies worldwide ( 40 ), however it remains the first leading cause of cancer deaths in African women [( 2 ), Figure 3 ] . Human papillomavirus (HPV) types 16 and 18 are the most common etiological factors for the pathogenesis of cervical cancer in Africa ( 42 ). The reported prevalence rate of HPV was 97.0% in Malawi ( 43 ), 92.1% in South Africa ( 44 ), 90.7% in Ibadan Nigeria ( 45 ), and 69.8% in Maiduguri and Nigeria ( 42 ).…”
Section: Uterine Cervical Cancermentioning
confidence: 99%
“…Human papillomavirus (HPV) types 16 and 18 are the most common etiological factors for the pathogenesis of cervical cancer in Africa ( 42 ). The reported prevalence rate of HPV was 97.0% in Malawi ( 43 ), 92.1% in South Africa ( 44 ), 90.7% in Ibadan Nigeria ( 45 ), and 69.8% in Maiduguri and Nigeria ( 42 ). In fact, the HPV infection is usually cleared in the immunocompetent women ( 46 ).…”
Section: Uterine Cervical Cancermentioning
confidence: 99%
“…Genomic polymorphism studies of these latter strains might be helpful to better understand the mechanism of no‐persistence or elimination of HPV52 in Senegalese women 27 . Another characteristic of our population is the 38.6% rate of multi‐infection that we observed, a proportion higher than that found in other series which varied from 4% to 20%–30% depending on the clinical stages 5,28–31 . An association between multi‐infection and poor outcome of invasive cancer was reported in Brazil 29 and association of multiples infection and HIV infection was clearly identified in several studies 32,33,18 …”
Section: Discussionmentioning
confidence: 48%